(untitled) (Research, Society and Development, 2022)
Objective: To report the experience of an Education Program of Work for Health group during the new coronavirus pandemic using technological health education strategies. Methodology: Descriptive and qualitative experience report, experienced by an interprofessional group from the State University of Pará during the new coronavirus pandemic, through the use of light-hard technologies in the context of health education. Results: The group produced about 40 materials on various themes during the years 2020 and 2021. The productions has been ocurred four times a month and were supervised by the group’s preceptors, coordinator and tutor. Themes was chosen using the health calendar provided by the Ministry of Health. Conclusion: With the onset of the new coronavirus pandemic, the activities of program needed to be readjusted to the new reality. Thus, the use of the virtual devices as a materials for prevention and health promotion proved to be necessary for the continuation of the activities, in addition to strengthening care networks and promoting collaborative health practices.